Can the use of smokeless tobacco products be accepted as a harm reduction method in tobacco addiction? - (:unkn) unknown (AVES Ibrahim Kara, 2014)
The goal of smoking cessation treatment is to keep the patient completely away from tobacco and tobacco products. The aim of harm reduction strategies in tobacco control is to reduce the risks associated with tobacco use. In order to turn it into an opportunity, tobacco companies have developed smokeless tobacco products. Some epidemiological studies have reported that smokeless tobacco products are safer than tobacco smoke. However, this method is not completely harmless. In this review, we will discuss all aspects of tobacco harm reduction methods. © 2014 by Turkish Thoracic Society.
Keywords: Harm reduction; Smokeless tobacco products; Tobacco